Ultrasound assisted hydration of grains with sigmoidal behavior: kinetics of hydration, cooking, germination and nutrient incorporation - Miano Pastor, Alberto Claudio (2018)
This Thesis had as objectives to study the hydration process of grains with sigmoidal behavior, evaluating ultrasound technology to improve it, the possible effects on germination, cooking and a possible incorporation of nutrients. The work was developed in three parts. The first part consisted of describing the hydration kinetics of many grains to have a data bank of hydration kinetics, allowing further selections. Furthermore, this part compared the differences among grains hydration kinetics, associating them with the intrinsic properties of the grains and questioning some inferences previously published in the literature. The second part was related to study the effect of ultrasound on the hydration kinetics of grains with sigmoidal behavior, being studied Andean lupin, mung beans and white kidney beans. Further, the effect of ultrasound in combination with soaking water at high temperatures was studied to demonstrate if they have additive, synergic or antagonist effect. The effect of ultrasound technology was evaluated in the water uptake, extraction of components, germination and cooking kinetics. The third part consisted of studying and describing the incorporation of a nutrient inside the grains, taking advantage of the hydration process. Further, ultrasound was used to improve this incorporation. The main results of this work corroborate that the hydration process is a complex phenomenon, and many intrinsic properties of the grains causes the kinetics differences. In addition, the fact that only legume grains have sigmoidal behavior of hydration was proved. Further, the ultrasound accelerated the hydration process of grains with sigmoidal behavior without affecting the grain starch, improving the extraction of undesirable components, enhancing or hindering the germination (depending on the grain), but without affecting the cooking process. Another result was that the higher the soaking water temperature is, the lower the ultrasound effect on hydration is. Finally, regarding nutrient incorporation, a hydrophilic nutrient (iron) was incorporated in a grain during hydration process demonstrating that it is possible. The iron incorporation had the same behavior as the water uptake, suggesting similar mechanisms and phenomena of mass flow. In addition, the incorporated iron was attached not only to the bean cotyledon, but also mostly in the seed coat. Furthermore, ultrasound technology enhanced this process. The cooking process of the studied grains was improved, and its germination was hindered by the incorporated iron. In conclusion, ultrasound technology can be used for improving the hydration process of grains with sigmoidal behavior, being also practical for nutrient incorporation into grains.